2015
DOI: 10.1089/thy.2014.0371
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cognitive, Motor, and Driving Impairments in Severe Hypothyroidism

Abstract: Transient profound hypothyroidism is characterized by reversible depression, decreased fine-motor performance, slowed reaction times, and decreased processing speed. These data represent new empirical evidence that support the recommendation that complex activities requiring rapid responses, such as operating motor vehicles, should be avoided during hypothyroidism. This has broader implications regarding functional impairments and risk to public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…It has been shown that circadian rhythms control sleep and biological processes including cell regeneration, core body temperature variations, and hormone metabolism (Buysse et al ., 2005; Sharma and Kavuru, 2010). There is also evidence that changes in the metabolism, especially disorders of the thyroid function, may be associated with cognitive decline (Smith et al ., 2002) and specifically decrease in speed of processing (Montalvo et al ., 2014; Smith et al ., 2015). Furthermore, changes in the thyroid, especially hypothyroidism, is considered a reversible cause of secondary dementia in older adults (Horvath et al ., 1989; Cummings, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that circadian rhythms control sleep and biological processes including cell regeneration, core body temperature variations, and hormone metabolism (Buysse et al ., 2005; Sharma and Kavuru, 2010). There is also evidence that changes in the metabolism, especially disorders of the thyroid function, may be associated with cognitive decline (Smith et al ., 2002) and specifically decrease in speed of processing (Montalvo et al ., 2014; Smith et al ., 2015). Furthermore, changes in the thyroid, especially hypothyroidism, is considered a reversible cause of secondary dementia in older adults (Horvath et al ., 1989; Cummings, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the United Kingdom found that low-dose radioiodine plus thyrotropin alfa was as effective as high-dose radioiodine, with a lower rate of adverse events [4]. A recent study demonstrated reversible cognitive, motor and driving impairments in severe hypothyroidism [11]. It will be important to analyze the impact of different protocols for RAI ablation on long-term treatment outcomes, particularly recurrence rates, quality of life, and health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of individual symptoms of iatrogenic hypothyroidism may vary from patient to patient; however, the cognitive, motor and psychological deficitslinked to severe hypothyroidism and resulting in the impaired ability to operate machinery or drive vehicles -might have been underestimated. Driving motor vehicles such as cars or motorbikes, should be avoided in the severe hypothyroid state because of decreased finemotor performance and processing speed, and slowed reaction times (braking times were increased by 8.0%, equivalent to the motor slowing caused by alcohol ingestion at a blood concentration of 0.082 g/100 ml; this concentration is above the levels allowed within EU for driving) [3]. This is quite relevant since driving habits appear to be difficult to change in at least 30% of THW cases, irrespectively of a strong negative medical advice [4].…”
Section: Cost-effectiveness Profile Of Exogenous Tsh Therapy (Thyrogementioning
confidence: 99%
“…The benefits associated with the use of Thyrogen ® include avoidance of the symptoms of hypothyroidism, which include fatigue, weakness, constipation, depression, impaired memory and bodily pain. Recently, hypothyroidism has been associated with cognitive and motor impairments that are likely to constitute hazards in the operation of motor vehicles and a public safety risk [3]. Avoidance of hypothyroidism via Thyrogen ® therapy has been found to be associated with consequent better health-related quality of life, little or no productivity loss and a reduction in the need for GP visits or medications [4].…”
mentioning
confidence: 99%